2016
DOI: 10.5152/ucd.2014.2335
|View full text |Cite
|
Sign up to set email alerts
|

Appendix adenocarcinoma in an elderly patient from a nursing home

Abstract: Appendiceal malignancies are rare clinic entities. The clinical presentation of appendiceal malignancies is often atypical. Acute abdominal pain and acute appendicitis, which requires early surgical intervention, are the most common clinical presentations of appendiceal malignancies. In this case report, an adenocarcinoma of the appendix in a 64-year-old male from a nursing home has been presented. He had right lower quadrant pain for the last 5 days. On physical examination, he had significant guarding. Intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…We strictly recommend a consultation of the patient to a neuroimmunologist if it is possible. Previously the authors have reported unusual findings in the appendectomized patients [ 5 ]. Together with this case, were commend multidisciplinary approach to patient with right lower quadrant pain with suspicious or unusual presentations.…”
Section: Discussionmentioning
confidence: 99%
“…We strictly recommend a consultation of the patient to a neuroimmunologist if it is possible. Previously the authors have reported unusual findings in the appendectomized patients [ 5 ]. Together with this case, were commend multidisciplinary approach to patient with right lower quadrant pain with suspicious or unusual presentations.…”
Section: Discussionmentioning
confidence: 99%